2022
DOI: 10.1136/rmdopen-2022-002575
|View full text |Cite
|
Sign up to set email alerts
|

Postvaccination anti-S IgG levels predict anti-SARS-CoV-2 neutralising activity over 24 weeks in patients with RA

Abstract: ObjectivesTo correlate immune responses following a two-dose regimen of mRNA anti-SARS-CoV-2 vaccines in patients with rheumatoid arthritis (RA) to the development of a potent neutralising antiviral activity.MethodsThe RECOVER study was a prospective, monocentric study including patients with RA and healthy controls (HCs). Assessments were performed before, and 3, 6, 12 and 24 weeks, after the first vaccine dose, respectively, and included IgG, IgA and IgM responses (against receptor binding domain, S1, S2, N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Schmiedeberg et al reported an equivalent T cell response in a treated RA population compared with healthy controls after the COVID-19 vaccine. 16 They observed also in this study that only anti-COVID-19 IgG were lowered and IgA and IgM levels were maintained. Interestingly, Kapetanovic et al demonstrated that despite a decreased total immunoglobulin level following pneumococcal vaccination, the numbers of circulating total and vaccine-specific IgG or IgA producing plasmablasts did not differ between patients with RA with or without MTX.…”
supporting
confidence: 70%
“…Schmiedeberg et al reported an equivalent T cell response in a treated RA population compared with healthy controls after the COVID-19 vaccine. 16 They observed also in this study that only anti-COVID-19 IgG were lowered and IgA and IgM levels were maintained. Interestingly, Kapetanovic et al demonstrated that despite a decreased total immunoglobulin level following pneumococcal vaccination, the numbers of circulating total and vaccine-specific IgG or IgA producing plasmablasts did not differ between patients with RA with or without MTX.…”
supporting
confidence: 70%
“…Regarding the cellular response, data are scarcer than for humoral immunogenicity. Schmiedeberg et al found a similar T cell response in a treated RA population and healthy controls after the COVID-19 vaccine, although it declined earlier in patients with RA [ 17 ]. The preservation of the cellular response reaffirms the positive role of the COVID-19 vaccine even in patients in whom the humoral response may foreseeably be more affected due to the disease or its treatments, although it would be of great interest to know if temporary DMARD rest strategies also enhance cellular immunity in these patients.…”
Section: Resultsmentioning
confidence: 99%